Design an Opening Force Measuring Device for Balancing Clips - Rónai, László; Kovács, Péter Zoltán; Gál, Viktor (International Journal of Engineering and Management Sciences, 2021)
This paper deals with the development of a force measuring device to determine the opening force of different types of balancing clips. These elements can be used in the impellers of ventilators to rebalance the rotor. The measuring device contains a commercially available beam type load cell. The data processing is performed by Arduino Nano development platform with a 24-bit sigma delta A/D converter. The device is well applicable to determine the opening force of the clips in different opening distances.